Etika Politik dalam Perspektif al-Mawardi - Rashda Diana; Siswanto Masruri; Surwandono Surwandono (Universitas Darussalam Gontor, 2018)
In this era, political ethics seems to be no longer valid, but it is almost disappeared. The reality shows that politics is a place for fighting of powers and interests, so that there is a general tendency to justify any means to achieve goals. Political pragmatism has corrupted the political ethics of politicians. One of them is money politics applied by many politicians which could not educate people and should become a bad example of politics. Actually, the politicians should be good examples for the people. Therefore, a politician must make political ethics a benchmark of orientation and a normative view to carry out dignified power. The authors tried to explain the thoughts of al-Mawardi, a Muslim thinker who discussed political ethics in depth in order to solve political problems faced by the people today, then the ethical and dignified Islamic politics could possibly be applied. The political ethics described and built by al-Mawardi is ideal rebuild a better political life. In his ethical concept, al-Mawardi always stressed the necessity of a ruler to always obey the ethical and moral values that have been explained in the Qur’an and Sunnah. So, al-Mawardi tried to provide a solution to fix the condition of the people as well as to maintain political stability.